Seminar Kewirausahaan Pengembangan UMKM di Berbagai Platform BIC di Desa Kebon Agung - Ricy Ichlas Sutrisno; Mohammad Nuril Azizi; Tri Seno Anjanarko; Rommy Hardyansah; Dharma Setiawan Negara; Novritsar Hasintongan Pakpahan; Yayu Sriwahyuni Hamzah; Utami Puji Lestari; Eli Retnowati; Jahroni Jahroni (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
In recent years, the development of information technology has changed the global marketing paradigm, introducing a digital era that opens up new opportunities for Micro, Small and Medium Enterprises (MSMEs). However, MSME owners in Kebon Agung Village, Sukodono District, Sidoarjo Regency still face obstacles in understanding and utilizing the potential of digital marketing to increase the visibility of their products. To overcome this problem, students of the Real Work Lecture (KKN) at Sunan Giri University Surabaya held an entrepreneurship seminar. The seminar was designed to provide MSME owners with an understanding of the importance of digital marketing and human resource innovation in improving product quality and competitiveness. The study results indicated that MSME owners in Kebon Agung Village can increase their income through the implementation of effective digital marketing strategies.